Influences of inattention on perceived self-efficacy, stress, and depression - Carriere, Jonathan S. A.; Nelson, Andrea L.; Cheyne, James Allan; Smilek, Daniel (Frontiers in Cognition, 2023)
Previous research provides indirect evidence that going through life mindlessly may produce feelings of depression, suggesting that cognitive deficits can lead both directly and indirectly to emotional problems (Carriere, Cheyne, & Smilek, 2008). Under this hypothesis, there are numerous possible routes from attention to affective issues, including through the sense of self-efficacy – a judgement about our ability to successfully achieve goals – and the experience of psychological stress. We used structural equation modeling to assess pathways from everyday inattentiveness, through the presumed intermediate experiences of diminished self-efficacy and psychological stress, to the experience of depressive affect. We tested several predictions: 1) the frequency of attention lapses predicts depressive affect; 2) attention-related errors mediate effects of inattention in predicting both self-efficacy and stress; 3) self-efficacy and stress directly influence depressive affect. The results indicate the proposed Attention-to-Affect models are parsimonious and provide good fit overall, consistent with the view that everyday inattention contributes to the emotional distress that creates depression.